Significant cultural patterns and their references in the poetry of Safi al-Din al-Hilli - Shnaweh, Lect. Dr. Masar Ghazi (Thi Qar Arts Journal, 2022)
The emergence of cultural criticism at the end of the last century brought about a qualitative leap in the field of critical practice as a whole, as we see a distinct shift from criticism of literature to criticism of culture, which has become a focused discourse in this field. Cultural criticism often embraces culture and never separates from it. Just as it takes from every science a party that combines contextual and systematic approaches, even theories of reading and reception, criticism of reader response and deconstruction, as it was based on psychology, sociology and history and relied on everything that would happen in addition to literature as a cultural phenomenon. It is striking that cultural criticism is based on a central idea that stems from and returns to, which is the criticism of fairness, especially the cultural defects that are implicit in every discourse or that are hidden behind the linguistic textual fabric. what they are.    Al-Hilli’s poetry conceals cultural patterns in which reality is critiqued from a behavioral, economic, political and religious point of view, providing the reader with an integrated picture of his society. We have relied on the categories of cultural criticism as a floating critical activity that refuses to fall under any approach, and uses procedural tools of various sources, which belong to different sciences such as anthropology, psychology, and history.In order to answer the research questions and its problems, the research plan was as follows:Introduction: I tried through it to provide an overview and familiarity with the subject and its basic forms.The first requirement: the most important tributaries of cultural criticism and its background knowledge:1: The concept of cultural pattern2: systemic function3: the cultural sentence4: the cultural sentence5: The total metaphor* The second requirement: an overview of the social and poetic papers of the poet Safi al-Din al-Hilli (677-752 AH / 1277-1339 AD).